Lepidoptera diversity in Ndodang Forest, Ngawi, East Java, Indonesia - SRI UTAMI; PAMELIA NURYATMAN; NURUL KUSUMA DEWI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Utami S, Nuryatman P, Dewi NK. 2024. Lepidoptera diversity in Ndodang Forest, Ngawi, East Java, Indonesia. Biodiversitas 25: 4772-4780. The Ndodang Ngawi Forest is characterized by many species of teak (Tectona grandis) and rosewood (Dalbergia latifolia) trees that grow there, but the richness of its flora and fauna has not been explored and identified. Therefore, this study aimed to analyze the diversity of Lepidoptera in Ndodang Ngawi Forest, East Java, Indonesia, and the physicochemical environmental factors affecting their presence. The experiment was conducted from March to May 2023, where Rhopalocera (butterfly) analysis was carried out using the pollard transect method. This approach periodically monitored the presence of butterfly and the sweep net technique was used as the sampling method. Heterocera (moth) analysis was carried out using a light trap technique determined by the purposive sampling method. A total of three study stations were set, namely the area in forest, edge, and riverbank areas. The results of the Lepidoptera study recorded 8 families, consisting of 37 species and 639 individuals, with Nymphalidae and Catopsilia pomona being the most prevalent, while Papilionidae family, Elymnias hypermnestra had 2 individuals. In addition to the influence of plant vegetation, the diversity of Lepidoptera species was also affected by environmental physicochemical factors. The air temperature of the Ndodang Forest with an average of 29.3OC, humidity of 65%RH, and light intensity of 3629 lux contributed to the survival of these species. Diversity data were processed using Microsoft Excel, including the Shannon-Wienner diversity, Evenness, and Simpson Dominance indices. Based on the analysis, the values obtained were categorized as medium (1<H'<3), indicating moderate diversity, species evenness was large (E> 0.6), and there were no dominating species (D < 0.5). Lepidoptera diversity in the Ndodang Forest is in the medium category. The evenness index shows the even distribution of the population in the Ndodang Forest area, so that the dominance index is relatively low in this area or there is no dominance of certain types of butterfly species. The diversity of Lepidoptera species is influenced by the presence of vegetation which is a source of food and also environmental physico-chemical factors such as air temperature, light intensity and air humidity. The more and more diverse types of vegetation that provide food sources, the greater the diversity of Lepidoptera.